Tracking Subsystem in Satellite - Bhakti Bhalchandra Sonule; Kanchan Kakde (International Journal of Satellite Remote Sensing, 2024)
The central nervous system and operating system of all satellite and spacecraft missions is called Satellite Telemetry, Tracking and Control (STT&C). Ground controllers can keep an eye on and manage the spacecraft's position, velocity, and location thanks to the tracking subsystem of the satellite. A key component of satellite TV for PC operations is tracking, which makes sure that satellites maintain their precise orbits and the right attitude to complete their tasks. To monitor and adjust satellite orbits and orientations as necessary, this requires a combination of ground-based tracking stations, telemetry data, and certain control systems. Additionally, data from sensors and satellite payloads are gathered using it. Various tracking methods might be employed based on the requirements of the task. It is first important to investigate ways to increase the GPS's navigation solution accuracy to augment the IRNSS with GPS. Satellite-receiver geometry, which describes the geometrical placements of the Navigation satellites observed by the GNSS receiver, affects the accuracy of the GPS navigation solution even while the delay problems caused by air layers and multipath are reduced. Doppler tracking, angle tracking, and distance tracking are a few popular tracking methods. This study evaluates the advancements achieved and the elements required for the design and execution of the tracking subsystem, encompassing significant satellite components.
Keywords: Tracking; angle tracking; attitude; doppler tracking; range tracking; subsystem